Low power reconfigurable sub-band filter bank ASIC for MP3 decoder - Gangamamba, B. P.; Muralidhar, Pendyala V.; Murthy, Nukala Satyanarayana (Inderscience Publishers, 2012)
Link to publisher's homepage at http://www.inderscience.com/